Targeted cleavage of mRNA in vitro by RNase P from Escherichia coli. - Li, Y (1992)
External guide sequences (EGSs) complementary to mRNAs that encode beta-galactosidase from Escherichia coli and nuclease A from Staphylococcus aureus can target these RNAs for cleavage in vitro by RNase P from E. coli. Specific cleavage occurs at locations predicted by the nucleotide sequences of the EGSs. EGSs with regions complementary to the mRNAs that are as short as 13 nucleotides function efficiently and turn over slowly during incubation with the target substrate and the enzyme. EGSs composed of deoxyribonucleotides as well as those composed of ribonucleotides are effective, but cleavage of the targeted substrate with DNA as an EGS is about 10-fold less efficient than that with RNA as an EGS. An RNA EGS inhibited the formation of beta-galactosidase activity in a crude extract (S30) of E. coli that was capable of catalyzing coupled transcription-translation reactions.